Formation of Integrated Sheep Village as Effort to Bring Livestock Technology to Farms Community - ., Isbandi (Indonesian Animal Sciences Society, 2013)
Establishing of âIntegrated Sheep Villageâ is one of the dissemination models as well as the media to introduce the technology to farmer. The model can be used as an effort to bring the technologies that have been produced by IRIAP to users (stakeholders). Indonesia Research Institute for Animal Production (IRIAP) has introduced a livestock production model known as